TRANSLATION AND TRANSFORMATION: THE EVOLUTION OF SINDHI LITERATURE AND CULTURE IN THE PRE-INDEPENDENCE ERA (1850-1947) - Sharma, Jayesh Durgadas; Sethi, Harish Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The period from the mid-19th century to 1947 witnessed a remarkable transformation in Sindhi literature, primarily driven by the translation of texts from Persian, English, Hindi and other Indian Languages. These translations introduced Sindhi readers to diverse literary forms and genres while preserving indigenous cultural narratives in the face of rapid socio-political changes. Prominent translators such as Mirza Qaleech Baig, Mangharam Udharam Malkani, Diwan Dayaram Gidumal and Allama I. I. Kazi played a pivotal role in this literary evolution. Their efforts not only enriched Sindhi literature but also stimulated intellectual and cultural discourse by making global literary ideas accessible to local audiences. This study delves into the profound impact of translated works on the literary and cultural landscape of Sindh, highlighting how these efforts facilitated the adaptation of foreign literary traditions while maintaining the region’s unique heritage. Moreover, the influence of translations on socio-political thought during this period is explored in detail. By analyzing the contributions of key translators and examining factual data, this paper underscores the vital role of translation as both a catalyst for literary development and a medium for cultural exchange in pre-independence Sindh.